2017
DOI: 10.1088/1741-4326/aa739c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neutral particle dynamics in Aditya tokamak plasma with DEGAS2 code

Abstract: Neutral particle behavior in Aditya tokamak, which has a circular poloidal ring limiter at one particular toroidal location, has been investigated using DEGAS2 code. The code is based on the calculation using Monte Carlo algorithms and is mainly used in tokamaks with divertor configuration. This code has been successfully implemented in Aditya tokamak with limiter configuration. The penetration of neutral hydrogen atom is studied with various atomic and molecular contributions and it is found that the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Details of these reactions are given in Refs. [44,45] which indicate that the plasma in the SOL region consists of electrons, + , + 2 , and 2 molecules mainly. Details of the model equations and normalization of each parameter have been given in [33].…”
Section: Modelling Using Bout++mentioning
confidence: 95%
“…Details of these reactions are given in Refs. [44,45] which indicate that the plasma in the SOL region consists of electrons, + , + 2 , and 2 molecules mainly. Details of the model equations and normalization of each parameter have been given in [33].…”
Section: Modelling Using Bout++mentioning
confidence: 95%
“…The radial profile of the electron temperature (T e ) is reconstructed based on measured values of the central temperature from Soft X-Ray (SXR) intensity ratio and the edge temperature from Langmuir probes and spectroscopy. The n e and T e measurements in the Aditya tokamak have been described in details by Chowdhuri et al [9] and Dey et al [16]. Based on the nature of the measured profiles, the values a = b = 1.32, in Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…The radial emissivity profiles (ph m −3 s −1 sr −1 ) [16,17] of a given impurity ion with charge state Z is obtained using the equation: E z (r) = n e (r) n z, g (r, t = t s ) PEC exc z (r) + n e (r) n z+1, g (r, t = t s ) PEC rec z+1 (r) + n H (r) n z+1, g (r, t = t s ) PEC cx z+1 (r) 4π…”
Section: Theorymentioning
confidence: 99%
“…It has been found that the neutral particles not only play an important role in the modification of the edge plasma dynamic, but also take active part in pedestal formation in the high confinement (H-mode) plasma in the tokamak [2]. Consequently, the study of the neutral particle dynamic has become very important, and it is mostly done through the investigation of neutral particle penetration into the plasma's central region through the modeling of the experimentally observed H α emissivity using neutral particle transport code [3,4]. The role of various atomic and molecular reaction pathways involved in producing the Balmer line (having a transition from the n = 3 to the n = 2 state) of the hydrogen has also been investigated as the product of the hydrogen atom having different temperatures [4][5][6], influencing the neutral particle dynamic inside the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the study of the neutral particle dynamic has become very important, and it is mostly done through the investigation of neutral particle penetration into the plasma's central region through the modeling of the experimentally observed H α emissivity using neutral particle transport code [3,4]. The role of various atomic and molecular reaction pathways involved in producing the Balmer line (having a transition from the n = 3 to the n = 2 state) of the hydrogen has also been investigated as the product of the hydrogen atom having different temperatures [4][5][6], influencing the neutral particle dynamic inside the plasma. These hydrogen particles are continuously generated by the charge exchange with the ions inside the plasma, and also by the interaction of ions with the plasma facing components (PFC), which recombine and are then re-emitted to the plasma as molecules.…”
Section: Introductionmentioning
confidence: 99%